REPRESENTASI NASIONALISME DALAM FILM HABIBIE DAN AINUN - Muhamad Aziz Musbihin; Alief Budiyono (Communicative : Jurnal Dakwah dan Komunikasi, 2024)
Ainun and Habibie is a film that has the second highest audience after Laskar Pelangi in Indonesia. Film Habibie and Ainun tell the story of Habibie life’s that has a tremendous love for his wife, family and country. Nationalism owned Habibie made him have to choose between his family and his country. Therefore, researchers are interested in analyzing the representation of nationalism owned Habibie and Ainun Habibie film so this research entitled "Representation of Nationalism In Film Habibie and Ainun". The focus of this research is how the representation of nationalism in the film and Ainun Habibie. This study used a qualitative method with semiotic analysis. Signs that represent nationalism in the film Ainun Habibie and the object of this study will be analyzed using the theory of semiotics John Fiske The Codes of Television. Data collection techniques in this research is the analysis of signs and literature.The results of this study is the ideology of nationalism which is owned by Habibie in the film Ainun Habibie and represented by means of speech, movement, expression and dialogue. So although the film Habibie and Ainun wrapped with drama romance between Habibie and Ainun, in this film there is the ideology of nationalism from a Habibie.